Packaging methodologies and processing techniques to extend shelf life of longan fruits (dimocarpus longan ) - Tuan Norsyuhada Tuan Mohd Ghazali (2013)
The main purpose of this study was about packaging methodologies and processing techniques to extend shelf -- life of longan fruits (Dimocarpus longan). There were five types of processing techniques that had been used were crunchy longan pickle, longan pickle, longan dried salted pickle, longan syrup and dried longan. The types of packaging methodologies used in this study were air tight containers, sealed plastic bag, glass jar and vacuum packaging. The duration period of the experiment was about two months. All of the data collected was analyzed using SPSS Software with Two Way ANOVA methods. From the observation, it was found that the most suitable processing techniques to extend shelf -- life of longan were crunchy longan pickle, longan dried salted pickle and dried longan since these three types of methods can extend the shelf —life of longan for about two months. For the packaging methodologies, all types of packaging were suitable to use for crunchy longan pickle, longan dried salted pickle and dried pickle since there were no significance difference occur between the usage of all four types of packaging besides for longan pickle and longan syrup. These were because the two types of longan processing techniques become rotten after one week of storage. In conclusion, the most suitable processing techniques to preserve the longan fruits were crunchy longan pickle, longan dried salted pickle and dried longan by using air tight container, sealed plastic bag, glass jar and vacuum packaging methodologies